Incidence of aflatoxins contamination in dry fruits and edible nuts collected from Pakistan. (August 2017) - Asghar, Muhammad Asif; Ahmed, Aftab; Zahir, Erum; Asghar, Muhammad Arif; Iqbal, Javed; Walker, Gavin
Abstract: During 2012–2015, a total of 624 samples of 13 different types of dry fruits and edible nuts were collected from retail shops and local markets of Pakistan. The collected samples were then studied for the occurrence of total aflatoxins (AFs) after immunoaffinity cleanup followed by HPLC coupled with fluorescence detector and post-column derivatization unit (Kobra Cell™). The seasonal variation of AFs was studied with respect to average temperature and relative humidity in Pakistan. LOD (S/N; 3:1) and LOQ (S/N; 10:1) of the utilized method were in the range of 0.09–0.12 and 0.30–42 μg/kg, respectively. About 165 (26%) samples were found contaminated, ranging from 0.22 to 30.11 μg/kg with a mean equivalent to 0.85 ± 0.26 μg/kg. In 459 (74%) samples, the AFs contamination was found lower than detectable limit corresponding to0.12 μg/kg. In 99 (15%) samples, the contamination range of AFs was 1–4 μg/kg. However, 28 (4%) samples exceeded the maximum tolerated limit (MTL) of 4 μg/kg as imposed by EU. However, 6 (1%) samples were found beyond the MTL of20 μg/kg as regulated by USA. Highly contaminated samples were found during the months of July, August and September. Achieved data highlighted the requirement of continuous monitoring and further investigation of AFs contamination in dry fruits/edible nuts under the authority of a definite systematic surveillance program adapted as a food safety measure. Highlights: The occurrence of AFs in dry fruits and edible nuts from Pakistan were assessed. Samples 165/624 were found positive with aflatoxins contamination. The contamination range was 0.22–30.11 μg/kg with a mean level 0.85 ± 0.26 μg/kg. The seasonal variation of AFs was studied with respect to temperature and RH. AFs level was compared with reported levels in national and international community.